Unraveling and resolving inefficient glucolipid biosurfactants production through quantitative multiomics analyses of Starmerella bombicola strains. Issue 2 (12th November 2019) - Lodens, Sofie; Roelants, Sophie L.K.W.; Ciesielska, Katarzyna; Geys, Robin; Derynck, Evelien; Maes, Karolien; Pattyn, Filip; Van Renterghem, Lisa; Mottet, Léopold; Dierickx, Sven; Vanhaecke, Lynn; Devreese, Bart; et al.
Abstract: Glucolipids (GLs) are glycolipid biosurfactants with promising properties. These GLs are composed of glucose attached to a hydroxy fatty acid through a ω and/or ω‐1 glycosidic linkage. Up until today these interesting molecules could only be produced using an engineered Starmerella bombicola strain (∆ ugtB1 :: URA3 G9) producing GLs instead of sophorolipids, albeit with a very low average productivity (0.01 g·L −1 ·h −1 ). In this study, we investigated the reason(s) for this via reverse‐transcription quantitative polymerase chain reaction and Liquid chromatography‐multireaction monitoring‐mass spectrometry. We found that all glycolipid biosynthetic genes and enzymes were downregulated in the ∆ ugtB1 G9 strain in comparison to the wild type. The underlying reason for this downregulation was further investigated by performing quantitative metabolome comparison of the ∆ ugtB1 G9 strain with the wild type and two other engineered strains also tinkered in their glycolipid biosynthetic gene cluster. This analysis revealed a clear distortion of the entire metabolism of the ∆ ugtB1 G9 strain compared to all the other strains. Because the parental strain of the former was a spontaneous ∆ ura3 mutant potentially containing other "hidden" mutations, a new GL production strain was generated based on a rationally engineered ∆ ura3 mutant (PT36). Indeed, a 50‐fold GL productivity increase (0.51 g·L −1 ·h −1 ) was obtained with the new ∆ ugtB1 :: URA3 PT36 strain compared with the G9‐based strain (0.01 g·L −1 ·h −1 ) in a 10 L bioreactor experiment, yielding 118 g/L GLs instead of 8.39 g/L. Purification was investigated and basic properties of the purified GLs were determined. This study forms the base for further development and optimization of S. bombicola as a production platform strain for (new) biochemicals Abstract : The authors describe the investigation of the reason(s) for a low glucolipid (GL) production by an engineered Starmerella bombicola strain via RT‐qPCR, LC‐Multi Reaction Monitoring (MRM)‐MS and metabolomics. They found a clear distortion of this strain on all levels due to a bad background. A new GL production strain was generated based on these findings. A 50 fold productivity increase was obtained with the new strain. Purification was investigated and basic properties of the purified GLs were determined, unravelling high potential for application of these molecules.